A collection of optical solitons for the concatenation model in the presence of multiplicative white noise and spatio-temporal dispersion - Wedad Albalawi; Nauman Raza; Saima Arshed; Evren Hincal; Saud Owyed; Kottakkaran Sooppy Nisar; Mohammed Zakaria (Alexandria Engineering Journal)
The extraction of novel optical solitons for the proposed model, which includes Kerr law nonlinearity, space–time dispersion, different Hamiltonian perturbation terms, and the effect of multiplicative white noise, is the aim of this work. A complete set of soliton solutions is obtained by applying three different expansion strategies. The final findings are visualized graphically via surface graphics, density plots and 2D plots to illustrate the behavior noise phenomenon on obtained solutions. These visual depictions shed light on various aspects of the equation’s dynamics and offer invaluable insights. Our computational analysis serves to verify the effectiveness and adaptability of our methodologies in addressing a broad class of nonlinear problems in mathematical science and engineering. This research communicates new avenues for our understanding of optical phenomena and provides a useful insight of how solitons behave in the presence of noise.